BIOFUEL PRODUCTION, SILVER NANOPARTICLE EXTRACTION AND THE THERAPEUTIC ANALYSIS FROM JATROPHA CURCUS SEEDS USING MICROBES BY SOLID STATE FERMENTATION - Dsvgk Kaladhar1, Meesala Sudhakar2*, Dharmendra Kashyap3, Nikki Agrawal4, Kamleswar5, Leena Preeti Lakra6, Smriti Pandey7 , Purnima Gupta8, (Chelonian Research Foundation, 2023)
Biodiesel is the most common biofuel produced in Europe by transesterification of vegetable, animal, and algal lipids. It is utilized as a fuel in its pure form (B100) and includes methyl/alkyl esters of long-chain fatty acids. About 100 g of Jatropha curcas seeds were fed into the oil extraction machine, and the oil was extracted according to the machine's operating process at 210 °C and the Jatropha curcas seeds produced around 42% seed oil. The pink color cocci was observed in the gram staining for microorganism isolated from water bodies of Arpa river, Bilaspur (CG) shows the presence of gram negative bacteria (probably E.coli). The antibacterial activity of microbial oil extracts, and Jatropha curcas seed oil was tested. The Candida, E. coli, Neurospora, and Staphylococcus, the seed oil hasn't demonstrated any effectiveness. Petroleum ether or ethanol that was dissolved in microbial oil (50:50) showed less antibacterial action. Keywords: Jatropha curcas seeds, Biofuel, antimicrobial activity, oil extraction, gram staining